Impact of insecticide exposure method on susceptibility/resistance in Aedes albopictus mosquitoes - Slade, Raven (East Carolina University, 2022)
Insecticide resistance is a concern of mosquito control programs (MCPs) whose primary function is to protect public health. Mosquitoes can develop resistance over time when exposed to sublethal doses of insecticide active ingredients (AIs). Resistance to AIs renders them ineffective as a preventive measure for the risk of mosquito-borne diseases. Mosquito exposure to insecticides during ultra-low volume (ULV) application occurs via direct liquid contact (formulated product [FP]), while barrier applications expose mosquitoes to dried residual FP. The Centers for Disease Control and Prevention (CDC) bottle bioassay (based on contact with dried residual insecticide AI) may not directly relate to operational interventions for ULV applications. Hence, the current study assesses how topical/direct versus residual insecticide exposure impacts mosquito susceptibility/resistance to pyrethroid (permethrin) and organophosphate (malathion) AIs. Female Ae. albopictus (4–5-d old) were aspirated from a colony cage and anesthetized with cold. Mosquitoes were either treated topically with 1 µL of each AI (stocks made in acetone) or transferred to bottles containing 1 ml of residual AI as used in CDC bottle bioassays (400 µg/mL malathion; 8 µg/mL permethrin for topical and residual treatments). Control groups were treated with acetone instead of AIs (following topical and residual exposure methods). Immediately after topical exposure and 10-15 min after residual exposure, each group was transferred to separate 0.5 L cardboard cages (7 mosquitoes/cage; 2 replicate cages/group). Mosquitoes were provided 20% sucrose and placed in a 28°C incubator with 14 h light:10 h dark. Mortality was monitored/recorded for all groups 1 h, 2 h, and 24 h post-exposure. Topical exposure to malathion (50, 83, 100% mortality at 1, 2, 24 h post-exposure) showed higher mosquito mortality compared to residual exposure (0, 36, 36% mortality 1, 2, 24 h post-exposure). Both exposure methods showed high mosquito mortality for permethrin (topical: 69, 100, 100% dead 1, 2, 24 h; residual: 71, 100, 100% dead 1, 2, 24 h). No mortality was observed in control groups. Investigators plan to conduct a larger scale experiment using a field-collected Ae. albopictus population in the future.
Keywords: insecticide resistance; mosquitoes; susceptibility